Metagenome sequencing to unveil microbial community composition and prevalence of antibiotic and metal resistance genes in hypersaline and hyperalkaline Lonar Lake, India - Chakraborty, Jaya; Sapkale, Vibhavari; Shah, Manan; Rajput, Vinay; Mehetre, Gajanan; Agawane, Sachin; Kamble, Sanjay; Dharne, Mahesh (Ecological Indicators, 2020)
Lonar Lake (India) is a hyperalkaline and hypersaline soda lake encompassing unique microbial composition and functions. This ecosystem has not been explored for taxonomic diversity and functional aspects (with emphasis on antibiotic and metal resistance genes) using whole metagenome sequencing for multiple years. Bacterial diversity analysis during year 2013, 2016, and 2018 depicted differences in the dominance of Proteobacteria, Firmicutes and Bacteroidetes. For archaeal diversity, a similar pattern persisted with higher abundance of Euryarchaeota. Functional metagenome analyses, indicated presence of antibiotic resistance gene (ARG) and metal resistance gene (MRG) profiles in the lake. A wider continuum of resistance genes with dominant ARG types as multidrug resistance efflux pumps and beta-lactams were also observed. The lake resistome demonstrated fluoroquinolone and acriflavine resistance genes indicating sewage water contamination in the lake. The MRGs linked with resistance to toxic metals (arsenic, cobalt, cadmium, copper, and zinc) and cation efflux protein CusA and cobalt-zinc-cadmium resistance protein revealed metal contamination. This study could be a baseline for understanding prevalence of antibiotic and metal resistance mechanisms resulting from various anthropogenic activities nearby lake, and find integrated approaches for conservation of the precious Lonar Lake ecosystem.
Keywords: Archaeal diversity; ARGs; Bacterial diversity; Illumina sequencing; Lonar lake; MRGs

Magnetically separable Brønsted acid catalyst for the synthesis of Bisguaiacol-F - Tarade, Komal; Rode, Chandrashekhar; Kamble, Sanjay (New Journal of Chemistry, 2025)
Currently, polycarbonates, epoxy resins, and plastics are commercially made from Bisphenol-A. However, BPA-containing materials are well known for causing major health problems and have been banned in several countries. To address this concern, Bisguaiacol-F (BGF) has been developed as a safer and more sustainable alternative to Bisphenol-A. We created a novel sulfonic acid-functionalized, magnetically separable heterogeneous Br & oslash;nsted acid catalyst, [Fe3O4@SiO2-(Pr)3-N-Bu-SO3H][HSO4-], which was successfully utilized for the manufacture of BGF by condensing 37% aq. formaldehyde with two molecules of guaiacol. The main objective for this reaction was to avoid using excess guaiacol while also completing the conversion of both starting components. Surprisingly, our manufactured catalyst promotes the complete conversion of aqueous formaldehyde and guaiacol into regioisomers such as pp `-BGF, mp `-BGF and op `-BGF with 62%, 15%, and 6% selectivity, respectively. Our novel magnetically separable heterogeneous catalyst has improved catalytic activity in terms of starting material conversion and product distribution, which can be attributed to its unique structural characteristics. It contains a pendant -SO3H group that is connected to a lengthy butyl chain, making it conveniently accessible in the reaction. We have created the framework for a promising and environmentally aware approach to the synthesis of Bisguaiacol-F by meticulously optimizing reaction parameters such as time, temperature, reactant molar ratio, and catalyst loading. The catalyst was extensively characterized using acid-base titration, FT-IR, XRD, TGA, and NMR techniques to confirm the structure and reveal remarkable stability and activity. Notably, the catalyst demonstrated recyclability across six consecutive runs, with no noticeable reduction in its effectiveness. The catalytic activity was also tested for guaiacol condensation with a variety of aldehydes to create Bisguaiacol derivatives.

Monitoring influenza A (H1N1, H3N2), RSV, and SARS-CoV-2 using wastewater-based epidemiology: A 2-year longitudinal study in an Indian megacity covering omicron and post-omicron phases - Pramanik, Rinka; Nannaware, Kiran; Malik, Vinita; Shah, Priyanki; Sangewar, Poornima; Gogate, Niharika; Shashidhara, L. S.; Boargaonkar, Radhika; Patil, Dhawal; Kale, Saurabh; Bhalerao, Asim; Jain, Nidhi; et al. (Food and Environmental Virology, 2025)
{The bourgeoning field of wastewater-based epidemiology (WBE) for the surveillance of several respiratory viruses which includes Influenza A, H1N1pdm09, H3N2, respiratory syncytial viruses (RSV), and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is of interest for public health concerns. However, there are few long-term monitoring studies globally. In this study, respiratory viruses were detected and quantified from 11 sewer sheds by utilizing reverse transcription-quantitative polymerase chain reaction analysis in Pune city, India, from Jan 2022 to Dec 2023. The RNA fragments of respiratory viruses were detected in sewage samples before clinical cases were reported, underscoring the potential of WBE for early detection and monitoring within the population. The Spearman correlation of wastewater viral copies was positively and significantly correlated with the clinically positive case of H1N1pdm09 (rho = 0.55
Keywords: Influenza A; Quantitative reverse transcription-PCR; Respiratory viruses; SARS-CoV-2; Wastewater-based epidemiology